The Impact of Impact-driven Entrepreneurship on Community Empowerment and Corporate Social Performance in Indonesia - Rahmat, Ariawan; Kusmiyatun, Kusmiyatun; Barus, Irwan Irawadi; Sudarmanto, Eko; Nurhayadi, Willy (Eastasouth Institute, 2025)
This study examines the impact of impact-oriented entrepreneurship on community empowerment and corporate social performance in Indonesia. As entrepreneurship increasingly moves beyond profit maximization toward addressing social and environmental challenges, impact-oriented entrepreneurship offers an integrated approach that prioritizes sustainability and inclusivity. Using a quantitative method, data were collected from 100 respondents through a structured questionnaire based on a five-point Likert scale. The analysis employed Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to test the hypothesized relationships. The results show that impact-oriented entrepreneurship has a positive and significant effect on community empowerment, reflected in greater participation, skills development, and resource access. In addition, impact-oriented entrepreneurship positively and significantly influences corporate social performance by improving stakeholder trust, ethical practices, and organizational legitimacy. The findings suggest that entrepreneurial ventures in Indonesia can serve as a catalyst for both social empowerment and sustainable business performance. This research contributes to the theoretical discourse on social entrepreneurship and corporate responsibility while offering practical insights for entrepreneurs and policymakers in designing strategies that balance financial success with social impact.